2019
DOI: 10.1021/acs.jnatprod.9b00317
|View full text |Cite
|
Sign up to set email alerts
|

Natural Alkaloid Berberine Activity against Pseudomonas aeruginosa MexXY-Mediated Aminoglycoside Resistance: In Silico and in Vitro Studies

Abstract: The multidrug efflux system MexXY-OprM, inside the resistance-nodulation-division (RND) family, is a major determinant of aminoglycoside resistance in Pseudomonas aeruginosa. In the fight aimed to identify potential efflux pumps inhibitors (EPIs) among natural compounds, the alkaloid berberine emerged as a putative inhibitor of MexXY-OprM. In this work, we elucidated its interaction with the extrusor protein MexY and assessed its synergistic activity with aminoglycosides. In particular, we built an in silico m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 68 publications
6
65
0
1
Order By: Relevance
“…Therefore, GlxII can represent a regulatory step of the glyoxalase pathway and for this reason the activity levels of GlxII do not always have the same trend as those of GLxI. Moreover, protein–protein interaction studies, performed using a validated in silico approach [ 50 ], have been shown that GlxII could catalyze protein S-glutathionylation using S-D-lactoylglutathione as substrate, on specific redox dependent proteins [ 39 ]. This capacity implies that S-D-lactoylglutathione formation from MGO and GlxII activity could play a relevant role in the regulation of cell metabolism and redox signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GlxII can represent a regulatory step of the glyoxalase pathway and for this reason the activity levels of GlxII do not always have the same trend as those of GLxI. Moreover, protein–protein interaction studies, performed using a validated in silico approach [ 50 ], have been shown that GlxII could catalyze protein S-glutathionylation using S-D-lactoylglutathione as substrate, on specific redox dependent proteins [ 39 ]. This capacity implies that S-D-lactoylglutathione formation from MGO and GlxII activity could play a relevant role in the regulation of cell metabolism and redox signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The computational protocol combining Blind/focused docking in triplicate [62,63] was applied for both Erl and EGCG in association with wild type, T790M/L858R and ELREA deletion-EGFR-receptor; the most stable EGFR-ligand complexes for each couple ligand-receptro were relaxed by 20 ns of MD simulation following the MD protocol previously described. Finally, to the stability and the interaction of Erl and EGCG bound with three different EGFR forms are evaluated and compared.…”
Section: Inhibitors Docking To Egcfr Receptorsmentioning
confidence: 99%
“…The resistance against antibiotics represents an important problem because the phenomenon involves different bacterial species which include Pseudomonas aeruginosa [ 5 ] and Escherichia coli [ 6 ]. Antimicrobial resistance genes (ARGs) can be transferred to other bacterial species and thereafter can lead to the production of various enzymes (such as beta-lactamases) that inactivate antimicrobial activities; the types of enzymes are myriad in carbapenemase-producing carbapenem-resistance Enterobacteriaceae (CP-CRE), and include clavulanic-acid-inhibited β-lactamases (Class A: Klebsiella pneumoniae carbapenemase, KPC; non-metallocarbapenemase, NMC; imipenemase, IMI; Serratia marcescens enzyme, SME; and Guiana extended-spectrum, GES), metallo-β-lactamases (Class B: Verona integron-encoded metallo-β-lactamase, VIM; New Delhi metallo-β-lactamase-1, NDM-1; German imipenemase, GIM; and Sao Paulo metallo-β-lactamase-1, SPM-1) and extended-spectrum oxacillinases (Class D: oxacillinase OXA-48-like) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%